DEVELOPMENT GUIDELINES FOR TOURISM DESTINATION TO SATISFY LIFESTYLE AND BEHAVIOR OF GENERATION Y - MULKUNEE, SURAPORN; ่Jaiuea Monrat; Suksathit, Kobkrit; Manomaikul, Peempiphat; Taraka, Petchampai (Thai Interdisciplinary and Sustainability Review, 2023)
This research aims to propose guidelines for tourist destination development that meets generation Y tourists’ lifestyles and behaviors. The population refers to 400 Thai generation Y tourists. The sample size is determined by using Taro Yamane formula while convenient sampling is used to identify the sample. A questionnaire is used as a data collection tool. The data analysis is performed by using descriptive statistics including percentage, mean, and standard deviation. According to the result, it appears that the lifestyles of generation Y tourists prefer to meet people, like to feast, like to dinning out, love to take picture and check-in, and always sharing information via social media. Therefore, there are eight ways to develop the tourist destinations to respond to generation Y tourists’ behaviors and lifestyles: 1) Develop facilities 2) Develop and elevate the potential of the tourist destination 3) Improve and elevate accommodations at the tourist destinations 4) Develop the tourist service in terms of tour packages 5) Develop and support tourism activities for generation Y 6) Develop the efficiency of the tourism services 7) Improve and develop the accessibility to the tourist destinations and 8) Encourage and support tourism marketing.